The Art of Misspelling: Unraveling the Diverging Effects of Misspelled Brand Names on Consumer Responses - Smith, Leah Warfield; Abell, Annika (Journal of Consumer Research, 2026)
Abstract Linguistic characteristics influence how consumers recognize and associate with brands. Although recent research shows the negative impact of misspellings in brand names on sincerity and brand attitudes, many brands successfully use this strategy to create unique brand identities. We argue that not all misspellings have the same negative impact and thus explore how consumers process brand names through both linguistic and conceptual fluency. In a series of six experiments, we present and examine a typology of misspellings and their differential impact on fluency and resulting consumer attitudes, inferences, and behavioral intentions. This typology of brand name misspellings provides a practical framework guiding brand naming strategy. We demonstrate that minor misspellings can be just as effective as correct spellings. More severe misspellings can also be effective if consumers perceive them as relevant. The findings reveal how managers can reap the benefits of misspelling, such as memorability, uniqueness, or trademark acquisition, and avoid the overall negative effects.